Severe complications induced by experimental bacterial superinfection of orf lesions - Zamri-Saad, M.; Roshidah, I.; Al-Ajeeli, Karim S. A.; Ismail, M. S.; Kamarzaman, A. (Kluwer Academic Publishers-Human Sciences Press, 1993)
Twelve goats about 3 months of age were divided into 4 equal groups. Goats in Groups 1 and 2 were infected with orf virus followed by Corynebacterium pyogenes infection of Groups 1 and 3, 3 days after the first appearance of orf lesions. Goats in Group 4 were uninfected controls. Complicated orf lesions which consisted of wet suppurative scabs around the entire lips were observed in goats in Group 1. The lesions persisted for 24 days but were most severe from days 8 to 13. Goats in Group 2 developed lesions typical of orf virus infection that lasted 10 days, while goats in Group 3 developed small nodules of about 1 cm diameter, 48 hours following the introduction of C. pyogenes, which persisted for only 6 days. No lesion was observed in goats in Group 4. Two goats in Group 1 with complicated orf died after 16 and 22 days respectively.